A Different Brain: Anomalies of Functional and Structural Connections in Williams Syndrome - Gagliardi, Chiara; Arrigoni, Filippo; Nordio, Andrea; De Luca, Alberto; Peruzzo, Denis; Decio, Alice; Leemans, Alexander; Borgatti, Renato (Frontiers in Neurology, 2018)
We describe the results of a functional and structural brain connectivity analysis comparing a homogeneous group of 10 young adults with Williams Syndrome (WS) (3 females, age 20.7±3.7 years, age range 17.4-28.7 years) to a group of 18 controls of similar age (3 females, age 23.9±4.4 years, age range 16.8-30.2), with the aim to increase knowledge of the structure–function relationship in WS. Subjects underwent a 3T brain MRI exam including anatomical, functional (resting state) and structural (diffusion MRI) sequences. We found convergent anomalies in structural and functional connectivity in the WS group. Altered FA values in parieto-occipital regions were associated with increased connectivity in the antero-posterior pathways linking parieto-occipital with frontal regions. The analysis of resting state data showed altered functional connectivity in the WS group in main brain networks (default mode, executive control and dorsal attention, sensori-motor, fronto – parietal, ventral stream). The combined analysis of functional and structural connectivity displayed a different pattern in the two groups: in controls the highest agreement was found in frontal and visual areas, whereas in WS patients in posterior regions (parieto-occipital and temporal areas). These preliminary findings may reflect an altered “wiring” of the brain in WS, which can be driven by hyper-connectivity of the posterior regions as opposed to disrupted connectivity in the anterior areas, supporting the hypothesis that a different brain (organization) could be associated with a different (organization of) behavior in Williams Syndrome.